Pengaruh Tingkat Penerapan GAP (Good Agricultural Practices) terhadap Pendapatan Petani Jagung (Analisis Regresi Linear di Kecamatan Tilongkabila) - Dwi Kurniawan Dondo; Ramlan Mustafa; Yanti Saleh (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2026)
This study analyzes the effect of the level of Good Agricultural Practices (GAP) implementation on maize farmers’ income in Kecamatan Tilongkabila. The GAP index was constructed from nine cultivation components based on Regulation of the Minister of Agriculture No. 48 of 2006, measured using a five-point Likert scale (1–5), then summed and normalized into a percentage index (0–100%). The study employed a survey of 30 purposively selected farmers and applied simple linear regression after meeting the classical assumptions. The results indicate a positive but very weak relationship between GAP and income (R = 0.260; R² = 0.067). The regression coefficient is B = 0.039 (t = 1.423; p = 0.166), meaning that a one-point increase in the GAP index is associated with an average increase of 0.039 income units. However, the effect is not statistically significant at α = 0.05. Therefore, this study does not provide sufficient statistical evidence that increasing the intensity of GAP implementation improves maize farmers’ income. Income variation is largely explained by factors outside the model, suggesting the need for further research incorporating more comprehensive variables. The present study enriches the body of knowledge in agricultural economics by employing a continuous GAP index to measure implementation intensity and by providing localized empirical evidence that GAP adoption, when implemented partially, may not automatically translate into higher farmer income.